PERENCANAAN GEOMETRIK JALAN TOL CIBITUNG – CILINCING INTERCHANGE TAMBELANG KABUPATEN BEKASI - Achmad Pahrul Rodji; Sahat Martua Sihombing; Qawi Ayadillah Hariyanto (Fakultas Teknik Universitas Krisnadwipayana, 2022)
The regencies of Bekasi, Karawang, and Purwakarta are experiencing rapid economic growth,because they are the center of the largest industrial area in West Java. This condition causes an increase intraffic on the Jakarta-Cikampek toll road to Jakarta or vice versa so that congestion often occurs. To overcomethese problems, it is necessary to build a toll road that can break down congestion on inner city toll roads, theCibitung - Cilincing toll road is made to reduce congestion on inner city toll roads because freight cars can godirectly to the port without having to go through the inner city toll road. . The purpose of this study is to planthe geometry of the toll road, especially in the access ramp section to and from the toll road. Geometricinterchange planning methodology by following the 2001 AASHTO standard, Procedures for GeometricPlanning for Inter-City Roads no. 038/TBM/1997, Geometric Planning Standards for Urban Roads 1992. Fromthese geometric plans selected 1 ramp located at the Tambelang interchange, the geometric planning analysisincludes vertical alignment, horizontal alignment the bend types used in the design include FC, SCS bends, andfor vertical alignments are concave and convex.